Contributions to Nephrology 2007
DOI: 10.1159/000100993
|View full text |Cite
|
Sign up to set email alerts
|

Body Protein Index Based on Bioelectrical Impedance Analysis Is a Useful New Marker Assessing Nutritional Status: Applications to Patients with Chronic Renal Failure on Maintenance Dialysis

Abstract: BPI calculated from measurement of multifrequency bioelectrical impedance analysis could evaluate whole body somatic protein stores, and is a potentially useful new marker assessing nutritional status in patients with chronic renal failure. Decreased body somatic protein stores, mainly due to muscle wasting, was prevalent in end-stage renal failure patients on maintenance dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…The finding is not new, yet its effects have not been fully established (25). Interestingly, BPI was significantly lower in this study population than in a comparable Japanese HD population, possibly due to ethnic differences (29). Establishing such differences before testing BPI as a marker of nutritional status seems necessary.…”
Section: Discussionmentioning
confidence: 72%
“…The finding is not new, yet its effects have not been fully established (25). Interestingly, BPI was significantly lower in this study population than in a comparable Japanese HD population, possibly due to ethnic differences (29). Establishing such differences before testing BPI as a marker of nutritional status seems necessary.…”
Section: Discussionmentioning
confidence: 72%
“…Instead, BIA has been reported to be a useful tool to measure body composition including muscle mass, fat mass and water volume because of its noninvasiveness, availability and simplicity. Recent developments regarding the precision of BIA devices and determination of the appropriate timing to estimate body composition in HD patients have enabled accurate measurement of the body composition in HD patients by BIA methods . Di Lorio et al.…”
Section: Discussionmentioning
confidence: 99%
“…One of its most studied utilizations is in patients on dialysis [38,39,40 ], especially because of the difficulty to perform anthropometric and laboratorial nutritional assessment of such patients. In their study of the prevalence of undernutrition in children on peritoneal dialysis, Edefonti et al [41] demonstrated that the electrical bioimpedance was more sensitive to body changes than the anthropometric measurements.…”
Section: Laboratory Assessment Of Body Compositionmentioning
confidence: 99%